ASSOCIATION OF INTRAVESICAL PROSTATIC PROTRUSION GRADE AND THE OUTCOME OF ALPHA BLOCKER TREATMENT FOR BLADDER OUTFLOW OBSTRUCTION - BUMBIA, HA; SOOMRO, NH; JAVED, A; ASLAM, MM; HIRAJ, GM; REHMAN, SU (Biological and Clinical Sciences Research Journal, 2023)
Benign Prostatic Hyperplasia (B.P.H) affects up to 80% of men older than 45 years of age worldwide, half of whom will eventually require treatment for its clinical manifestations such as bladder outflow obstruction (BOO) and its associated symptoms. There are various treatment strategies for B.P.H; alpha blockers being the most commonly employed. However, the outcome of said pharmacologic agent in treatment of BOO, in the presence of intra-vesical prostatic protrusion (IPP) of varying grades is less researched. The aim of the current study was to study the association IPP grade and the outcome of BOO treatment among patients with BPH. This prospective cohort comprised of a sample of 100 B.P.H patients, aged ≥ 45 years (chosen via non-probability – consecutive sampling), presenting to Ziauddin University Hospital, Karachi from June 2019 to December 2019. After taking written informed consent, data was recorded onto a pre-structured questionnaire containing inquiries pertaining to basic biodata, sociodemographic details, disease particulars, treatment outcome (gauged using IPSS, UFM and PVR) assessed at first contact and again after 1 and 3 months. The data obtained was analyzed using SPSS v. 21.0. The mean age of the sample stood at 68 years (SD ± 10.3).The mean prostate size was recorded to be 58 cm3 (SD ± 32) . The commonest grade of IPP was II (45%), followed by grade I (29%) and grade III (24%). The cumulative treatment outcome was poor, with only a meagre improvement (9.1% in IPSS score, 4% in UFM value and 13% in PVR) was recorded. Stratification revealed that the treatment outcome became progressively worse with increasing grade of IPP. After careful consideration, it can be concluded that the outcome of alpha blocker treatment for BOO among patients with IPP is poor. IPP serves to seemingly dampen the effect of alpha blockers with increasing grades corresponding to progressively worse outcome. Thus, additional modalities may be employed to supplement alphab blocker treatment for better patient outcome among patients with IPP.